Substantially improve the rates of foreign investment in Latin America - Salgado Defranc, José (Revista Universidad de Guayaquil, 2015)
Latin America and the Caribbean are becoming one of the most important centers of receiving FDI. This is confirmed by the fact that in 2012-2013 the regions as a whole caught superior to those achieved by United States amounts. In parallel, the amounts raised by Europe descend steeply (suffice to indicate that this low indicator of 40% of the world total in 2005-2008, to 20% in 2013). Conversely, looking at the process from the point of view of regions that invest abroad, indicate that in developing countries in 2013 flowed 39% of FDI in the world, when in 2010 this percentage was only 10% of the world total. These data indicate that we see profound changes in global geopolitics. In the study presented, then the role of Latin America in this process is analyzed.